Evaluation of Usnea barbata (L.) Weber ex F.H. Wigg Extract in Canola Oil Loaded in Bioadhesive Oral Films for Potential Applications in Oral Cavity Infections and Malignancy - Violeta Popovici; Elena Matei; Georgeta Camelia Cozaru; Laura Bucur; Cerasela Elena Gîrd; Verginica Schröder; Emma Adriana Ozon; Oana Karampelas; Adina Magdalena Musuc; Irina Atkinson; Adriana Rusu; Simona Petrescu; et al. (MDPI AG, 2022)
Usnea lichens are known for their beneficial pharmacological effects with potential applications in oral medicine. This study aims to investigate the extract of Usnea barbata (L.) Weber ex F.H. Wigg from the Călimani Mountains in canola oil as an oral pharmaceutical formulation. In the present work, bioadhesive oral films (F-UBO) with U. barbata extract in canola oil (UBO) were formulated, characterized, and evaluated, evidencing their pharmacological potential. The UBO-loaded films were analyzed using standard methods regarding physicochemical and pharmacotechnical characteristics to verify their suitability for topical administration on the oral mucosa. F-UBO suitability confirmation allowed for the investigation of antimicrobial and anticancer potential. The antimicrobial properties against Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27353, Candida albicans ATCC 10231, and Candida parapsilosis ATCC 22019 were evaluated by a resazurin-based 96-well plate microdilution method. The brine shrimp lethality assay (BSL assay) was the animal model cytotoxicity prescreen, followed by flow cytometry analyses on normal blood cells and oral epithelial squamous cell carcinoma CLS-354 cell line, determining cellular apoptosis, caspase-3/7 activity, nuclear condensation and lysosomal activity, oxidative stress, cell cycle, and cell proliferation. The results indicate that a UBO-loaded bioadhesive film's weight is 63 ± 1.79 mg. It contains 315 µg UBO, has a pH = 6.97 ± 0.01, a disintegration time of 124 ± 3.67 s, and a bioadhesion time of 86 ± 4.12 min, being suitable for topical administration on the oral mucosa. F-UBO showed moderate dose-dependent inhibitory effects on the growth of both bacterial and fungal strains. Moreover, in CLS-354 tumor cells, F-UBO increased oxidative stress, diminished DNA synthesis, and induced cell cycle arrest in G0/G1. All these properties led to considering UBO-loaded bioadhesive oral films as a suitable phytotherapeutic formulation with potential application in oral infections and neoplasia.